Restrictions on Freedom of Expression Under Chinese President Xi Jinping in the Globalization Era - Rusnandi Rusnandi (Papua Journal of Diplomacy and International Relations, 2022)
Much literature has highlighted the current Chinese government’s restriction on freedom of expression on the internet and religious freedom. However, very little research has examined the nexus between freedom of expression in China and globalization. This article aims to offer a view on President Xi Jinping’s increasing autocracy over the freedom of expression and its implications on China’s performance in this globalizing world. A qualitative approach was utilized in this study and data were collected via library research. It was found that China’s increasing autocracy under Xi Jinping, as shown in its tightening controls on online freedom of expression and rules on religious freedom, has created a setback for China’s participation in globalization. This argument lies in two basic assumptions. Firstly, the spirit of globalization enables people to interact around the globe more freely in any way, while China’s government restricts such interaction. Secondly, as a significant global player, China shows little respect for the freedom of religion. Accordingly, it violates the globalization of religious liberty, which is considered a universal human right in the 21st century. KEYWORDSChina; freedom of expression; globalization; religious freedom